2018
DOI: 10.11158/saa.23.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of Amblyseius largoensis to Raoiella indica eggs is mediated by previous feeding experience

Abstract: The mechanisms involved in the acceptance and choice of prey by predatory mites are still poorly understood. The present study was designed to determine whether previous feeding experience of Amblyseius largoensis (Muma) (Acari: Phytoseiidae) on Raoiella indica Hirst (Acari: Tenuipalpidae) eggs could influence the predator’s functional response and related parameters. The consumption of R. indica eggs by experienced and naïve female A. largoensis was evaluated under increasing densities of eggs. Regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Amblyseius largoensis, the third most numerous phytoseiid predator in association with R. indica in the present study, often has been reported in association with R. indica in the Neotropics, usually in coastal areas (Etienne & Flechtmann 2006;Rodrigues et al 2007;Roda et al 2008;Carrillo et al 2010;Hastie et al 2010;Carrillo et al 2011c;Gondim Jr. et al 2012;Moraes et al 2012;Flores-Gallano et al 2017). This predator has received the most attention as a possible candidate for practical use as biological control agent of the pest (Carrillo et al 2010;Carrillo et al 2011c;Carrillo et al 2012;Domingos et al 2012;Carrillo et al 2014;Morais et al 2016;Mendes et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Amblyseius largoensis, the third most numerous phytoseiid predator in association with R. indica in the present study, often has been reported in association with R. indica in the Neotropics, usually in coastal areas (Etienne & Flechtmann 2006;Rodrigues et al 2007;Roda et al 2008;Carrillo et al 2010;Hastie et al 2010;Carrillo et al 2011c;Gondim Jr. et al 2012;Moraes et al 2012;Flores-Gallano et al 2017). This predator has received the most attention as a possible candidate for practical use as biological control agent of the pest (Carrillo et al 2010;Carrillo et al 2011c;Carrillo et al 2012;Domingos et al 2012;Carrillo et al 2014;Morais et al 2016;Mendes et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The handling time and attack rate were estimated using non-linear least squares regressions from PROC NLIN of SAS (SAS Institute 2002). Since prey items were not replaced during the experimental period, the random predator equation of Rogers was appropriate to describe the type II functional response parameters (2) (Rogers 1972;Mendes et al 2018):…”
Section: Discussionmentioning
confidence: 99%
“…Thus we conducted the experiments on leaves of wolfberry, the original habitat of predator and prey. To avoid the deviation of feeding experience (Castagnoli & Simoni 1999;Mendes et al 2018), both phytoseiid species were uniformly fed with wolfberry mite galls for 30 days prior to bioassay. In addition, the type of functional response is not constant, which can be influenced by the alternative food and the stage of prey (Ganjisaffar & Perring 2015;Li et al 2018;Fathipour et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, species of the genus Brevipalpus Donnadieu are associated with the transmission of plant viruses that can cause diseases in important crops around the world (Childers et al 2003;Beard et al 2015;Roy et al 2015). In addition, the red palm mite, Raoiella indica Hirst, has recently received great attention due to its rapid spread and economic impact on palm crops in the New World (Flechtmann & Etienne 2004;Dowling et al 2008;Beard et al 2018;Mendes et al 2018).…”
Section: Introductionmentioning
confidence: 99%